Determinants of three-year clinical outcomes in real-world outpatients with bipolar disorder: The multicenter treatment survey for bipolar disorder in psychiatric outpatient clinics (MUSUBI). (July 2022) - Sugawara, Norio; Adachi, Naoto; Kubota, Yukihisa; Watanabe, Yoichiro; Miki, Kazuhira; Azekawa, Takaharu; Edagawa, Koji; Katsumoto, Eiichi; Hongo, Seiji; Goto, Eiichiro; Ueda, Hitoshi; Kato, Masaki; et al.
Abstract: Background: There is limited evidence regarding predictors of long-term clinical outcomes in patients with bipolar disorder (BD). The objective of this study was to describe 3-year clinical outcomes and identify their predictors from participants in the multicenter treatment survey for BD in psychiatric outpatient clinics (MUSUBI). Methods: The MUSUBI was a naturalistic study investigating patients with BD in real-world clinical practice. Our study extracted data regarding 1647 outpatients with BD from 2016, 2017, and 2019 as baseline, 1-year, and 3-year assessments. As clinical outcomes, we assessed the presence of time ill (depressive and manic) during the 1 year prior to the 3-year assessment and durable remission (53 weeks or more) prior to the 3-year assessment. Results: Participants with durable remission prior to the 3-year assessment had significant associations with diagnosis of a personality disorder and duration of continuous remission at baseline. Regarding the presence of depressive symptoms during the 1 year prior to the 3-year assessment, work status, Global Assessment of Functioning (GAF) scores, suicidal ideation, and duration of continuous remission at baseline had significant associations with this outcome. Conclusions: At the 3-year assessment, 19.3% of participants (318/1647) achieved durable remission, while 47.5% of them (782/1647) were not remitted. Our findings can help clinicians predict the illness course of BD by understanding demographic and clinical characteristics.